194 CONNECTED HEALTH SUSTAINING HOME STAY IN DEMENTIA (CHESS): SMART HEALTH TECHNOLOGY ACCEPTABILITY BY INFORMAL CAREGIVERS OF PEOPLE WITH DEMENTIA. (25th October 2022) - Blake, C; Merriman, N; Mackey, L; Fernandez, EG; Curran, F; Caulfield, B; O'Shea, D; Doyle, R; Power, D
Abstract: Background: The prevalence of dementia is increasing worldwide, and innovative strategies are required to meet increasing demands on health services. The Connected HEalth Sustaining home Stay in Dementia (CHESS) Study aimed to provide support to People with Dementia (PwD) and their caregivers in their homes. We aimed to quantitatively assess the acceptance of smart connected health technology by caregivers of PwD through use of standardised questionnaires. Methods: Fifty-two PwD and their informal caregivers were recruited by convenience sampling to the intervention arm of the CHESS Study. An additional 25 dyads acted as control participants. Questionnaire data were collected following completion of the CHESS study from 27 informal caregivers from the CHESS Technology group and 16 informal caregivers from the Control group. Measures of health technology acceptability included the System Usability Scale (SUS), the eHealth Literacy Scale (eHEALS), the Technology Readiness Index 2.0 (TRI), and the Unified Theory of Acceptance and Use of Technology Scale (UTAUT). Univariate analyses of variance were used to explore differences between groups. Results: Internal consistency (Cronbach's alpha) was high for all measures (range 0.68 – 0.96). The SUS score for the technology group was high (M=70.07, SD=17.69), indicating that the CHESS technology had a high level of usability. All participants had a high level of eHealth literacy (M=33.61, SD=10.51). Both groups performed similarly on the TRI and UTAUT, however the control group indicated greater discomfort with health technology and felt less secure in providing their personal information electronically to healthcare professionals than the technology group. Conclusion: Caregivers across the technology and control groups had high levels of eHealth literacy and found health technology to be generally acceptable. The CHESS technology in particular was rated as highly usable on the SUS by those who used it. These findings offer support for a Connected Health model of care.